An analysis of the performance of selected library schools in Metro Manila based on the Librarians' Licensure Exam (LLE) results - Caldo, Michael L.; Faderon, Rosalie B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2011)
This study aimed to determine whether the factors such as the faculty and students, admission and retention policies of LIS schools, facilities/tools, and curriculum led to the attainment of high performance of non-performance in the librarians' licensure examination of the selected library schools. This study was limited to selected library schools within Metro Manila, namely Philippine Normal University (PNU), Polytechnic University of the Philippines (PUP), University of the Philippines (UP), and University of Santo Tomas (UST).
The study was done through survey questionnaires, interviews and documentary analysis. Interviews were conducted with the heads of the departments of the chosen schools. Students from the library schools were surveyed to know their motivation in pursuing and finishing LIS. Documents on admission and retention policies and curriculum were also obtained as supplement to the interviews. Follow-up visits were also done to elicit clarifications from the respondents. The data and documents gathered were tabulated and then analyzed by statistical methods such as frequency counts, percentages and ranking.
One of the main conclusions of the study was that library schools with the high number of faculty, more and updated tools and facilities, tighter admission and retention policies may lead to better school performance in LLE. The student motivations and LIS subjects reflective of the coverage of the Librarians Licensure Examination were not that much different among the four library schools.
The researcher recommended that the library school should increase the number of full-time faculty members teaching LIS subjects as well as part-time, should set more specific or tighter admission and retention policies for students, should acquire more and update their tools and facilities in teaching Library and Information Science, especially in having their own computer laboratory. It was also recommended that library schools should be more cooperative in this kind of research since the research's primary goal is not to criticize but to help in improving the existing system of BLIS degree program.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Library schools -- Philippines -- Manila Metropolitan Area; Librarians -- Examinations